Participation and Perception of Generation Z of Menganti Villages in the Regional Election Campaign on Social Media - Mutiara Anjeli; Dwi Riswanda Imawan; Triphanie Obligar (Journal of Religion, Local Politics, and Law, 2025)
The democratic process of the Regional Elections is developing along with the development of digital technology. Social media has emerged as a key instrument for political campaigns especially when it comes to connecting with Generation Z. They have extensive access to social media and their opinions on online political campaigns reflect their level of participation. This study is to examine how Generation Z in Menganti Village participates in the Pilkada campaign on social media and how they perceive the effectiveness and credibility of the campaign. The methodology of this research is qualitative, and data is collected through campaigns on social media platforms including WhatsApp, Instagram, and TikTok as well as interviews. The results of the study show that adolescents' participation in the Pilkada campaign on social media varies, ranging from simply consuming information to being active in discussions and the dissemination of political content. Digital literacy factors, political preferences, and campaign strategies of candidates have a significant influence on their engagement. In addition, Generation Z's perception of political campaigns on social media tends to be diverse; Some consider it an educational source of information, but others feel that the campaign is full of hoaxes and propaganda. By understanding the patterns of participation and perception of Generation Z in the Pilkada campaign on social media, this research is expected to contribute to increasing digital political literacy as well as a more inclusive and transparent campaign strategy for the younger generation.